2018
DOI: 10.3344/kjp.2018.31.3.206
|View full text |Cite
|
Sign up to set email alerts
|

The impact of caudally administrated tramadol on immune response and analgesic efficacy for pediatric patients: a comparative randomized clinical trial

Abstract: BackgroundImmune responses appear to be affected by anesthetics and analgesics. We investigated the effects of caudal tramadol on the postoperative immune response and pain management in pediatric patients.MethodsSixty ASA-I pediatric patients aged 3–10 years undergoing lower abdominal surgery. Patients were randomly assigned either to a caudal bupivacaine (0.25%) group (group B), or a group that received caudal tramadol (1 mg/kg) added to the bupivacaine (0.25%) (group T). Both were diluted in a 0.9% NaCl sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…However, both groups began to recover gradually from 12 h after surgery, but the recovery rate of immune function in patients with dezocine was faster within 48 h after surgery. The variation tendencies of NK cells and T lymphocyte subsets were basically consistent with the results of previous studies (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…However, both groups began to recover gradually from 12 h after surgery, but the recovery rate of immune function in patients with dezocine was faster within 48 h after surgery. The variation tendencies of NK cells and T lymphocyte subsets were basically consistent with the results of previous studies (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…A study has shown that dexmetomide can effectively maintain the homeostasis of cellular immune function in patients undergoing radical mastectomy, can effectively improve the recovery of patients and reduce inflammation (15). Another study has reported that dexmetomide can effectively reduce the release of inflammatory factors in patients undergoing radical resection of gastric cancer and can reduce the decrease of CD3 + and CD4 + cells to improve the impairment of immune function (16). These studies have shown that drug PCIA has a positive effect on the immune function of the body.…”
Section: Discussionmentioning
confidence: 95%
“…In accordance, histopathological examination of different tissues, such as lung, heart and brain, after H & E staining, showed that tramadol was associated with less inflammatory cell infiltrates than tapentadol [ 55 ]. In this sense, considering tramadol analgesic potency and lower immunosuppressive effects, it was suggested as a better alternative for pain treatment than classical opioids, since it may have an immune enhancing effect and, thus, be especially considered in conditions where immunosuppression is contraindicated [ 80 , 85 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%